Clonal expansion dynamics on ART in individuals treated during acute and chronic infection. - Tine Struyve (22683295) (2025)
(A) Individuals are categorized into three groups according to ART initiation timing [during acute infection: Fiebig II-III (left panel), Fiebig IV-V (central panel); during chronic infection (right panel)]. Donut charts displaying the number of integration sites (IS) detected only once (white) or more than once (colored) at UD and UD + 5. Distinct clonal populations of infected cells are represented by different shades of pink. The total number of IS generated by ISLA for each participant is shown in the middle of each donut. (B) Pie charts displaying proportions of integration sites (IS) detected once (white) and more than once (pink). (C) Oligoclonality index for each individual of the Acute UD (n = 8), Acute UD + 5 (n = 5) and Chronic UD cohort (n = 3). Grey bars depict median values. Lines connect paired values for the longitudinally followed individuals in the acute cohort.